Fabrication, characterization and performance evaluation of an amplified electrochemical sensor based on MOFs nanocomposite for leukemia drug Imatinib determination - Biuck Habibi; Sara Pashazadeh (Sensing and Bio-Sensing Research, 2023)
In this research, the synthesis, fabrication steps and characterization of a new modified glassy carbon electrode (GCE) with CuFe2O4 magnetic nanoparticles combined with zeolitic imidazolate framework (ZIF-8) embedded graphene quantum dots (GQDs), (CuFe2O4/ZIF-8@GQDs), for electrodetermination of the imatinib (IMB), anti-cancer drug, are reported. The synthesized nanocomposite was characterized using X-ray powder diffraction (XRD), energy dispersive X-ray spectroscopy (EDX) and field emission scanning electron microscopy (FE-SEM). The GCE modified with CuFe2O4/ZIF-8@GQDs nanocomposite shows high electrocatalytic activity toward the oxidation of IMB compared with the bare GCE, GQDs/GCE, ZIF-8@GQDs/GCE, CuFe2O4/GCE and CuFe2O4@GQDs/GCE. The resulted electrocatalytic activity of the CuFe2O4/ZIF-8@GQDs/GCE can be attributed to the synergistic effect of the outstanding magnetic, electrical properties of the CuFe2O4/ZIF-8@GQDs and high conductivity of GQDs, as well as the high electron transport rate of the nanocomposite. Under optimized conditions, the developed sensor, CuFe2O4/ZIF-8@GQDs/GCE, has static properties such as wide linear range responses (0.02–11.85 and 11.85–94.20 μM), low detection limit (1.2 nM), high sensitivity (5.655 μA μM−1), long-term signal stability and reproducibility (RSD = 2.23%). It should be noted that the CuFe2O4/ZIF-8@GQDs/GCE sensor could be used for determination of IMB in biological and pharmaceutical samples, indicating its feasibility for real analysis.